2007
DOI: 10.1037/0882-7974.22.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Positive aspects of caregiving as a moderator of treatment outcome over 12 months.

Abstract: The authors examined the influence of positive aspects of caregiving (PAC) as a moderator of treatment outcome across 12 months in 1 of the original sites of the Resources for Enhancing Alzheimer's Caregiver Health I project. They used multilevel random coefficients regression analysis to predict time-varying PAC, depression, behavioral bother, and daily care burden in Alzheimer's caregivers (N = 243; mean age = 60.89, SD = 14.19). They found that time-varying PAC was predicted by time-varying daily care burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 73 publications
6
111
1
2
Order By: Relevance
“…Feeling overwhelmed by the demands of caregiving is related to poor mental health (Schwartz et al 2003). When caregivers perceive less burden, they experience positive aspects of caregiving and better well-being (Hilgeman et al 2007). …”
Section: Moderators and Mechanismsmentioning
confidence: 99%
“…Feeling overwhelmed by the demands of caregiving is related to poor mental health (Schwartz et al 2003). When caregivers perceive less burden, they experience positive aspects of caregiving and better well-being (Hilgeman et al 2007). …”
Section: Moderators and Mechanismsmentioning
confidence: 99%
“…Studies have found protective factors that could mediate or moderate caregiver burden [58,59,60,61]. A systematic review found finding meaning in caregiving and caregiver motivation to provide care has a positive impact on caregiver well-being [58].…”
Section: Coping With the Task Of Caregivingmentioning
confidence: 99%
“…The study suggested that providing support that would enhance the quality of life of the persons with dementia could indirectly help to alleviate the burden felt by family members caring for them [60]. Future studies need to explore the positive aspects of caregiving, such as the caregiver gain, protective factors that could mediate or moderate caregiver burden, and ways to promote caregivers’ resilience [61]. …”
Section: Coping With the Task Of Caregivingmentioning
confidence: 99%
“…The preservation of physical and mental health of family caregivers to dementia patients must be understood as an asset to the efficient and ethical fulfillment of this important role [7][8][9] . There is an estimate of 46% of increase in the demand for healthcare services for AD patient caregivers 10 . In addition, up to 60% of family caregivers to AD patients may develop physical and/or psychological symptoms, including hypertension, digestive problems, sleep disorders, respiratory diseases, immunologic system deficiency, depression, anxiety and insomnia 7,11 .…”
Section: Introductionmentioning
confidence: 99%